UK alcohol marketing regulation is failing: a new approach is needed to prioritise protection for all. (4th March 2023) - Boniface, Sadie; Atkinson, Amanda M.; Critchlow, Nathan; Jones, Michaela; Meadows, Beth; Severi, Katherine
Abstract: This commentary about alcohol marketing regulation in the UK draws on a conference held by the Institute of Alcohol Studies, highlighting a need for policy interventions to prevent harm and improve public health. Hazardous and harmful alcohol use is associated with many health conditions, wider social consequences, and harms to others. Following no improvement in alcohol mortality rates in the past decade, 2020 saw alcohol-specific deaths rise to record levels in the UK. Bans or comprehensive restrictions on alcohol advertising across multiple types of media are listed by the World Health Organization (WHO) as one of the 'best buy' policies to reduce alcohol harm. The UK's current complaints-led self-regulatory approach fails to protect consumers and vulnerable groups from being exposed to influential alcohol marketing. There are few meaningful sanctions to deter brands and companies from violating existing codes, processes are retrospective, reactive and slow, and the codes fail in their stated aim of protecting young people. Other important impacts on heavier drinkers and those in recovery, as well as on gender and health equity, are also inadequately addressed. Innovation is also urgently needed to effectively regulate ever-evolving digital alcohol marketing. Addressing these issues through a combination of comprehensive restrictions, content controls, labelling, and replacing self-regulation with an independent body will benefit public health as well as protecting the vulnerable, including heavier drinkers, people in recovery, and children and young people.